Pengaruh Green Intellectual Capital Terhadap Environmental Performance Dengan Green Human Resource Management sebagai Variabel Mediasi - Fattah, Muhammad Lutfi Ali; Nugroho, Sidiq Permono (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Green Intellectual Capital refers to the collective value of intangible assets, including information, skills, and connections, related to environmental conservation and innovation. These assets contribute to the promotion of environmentally friendly ideas and practices at both the individual and organizational levels within a company (Chen, 2008). Green Intellectual Capital consists of three distinct elements: Green Human Capital, Green Structural Capital, and Green Relational Capital. Adopting the concept of GIC is a strategic step for organizations to achieve competitive advantage while upholding environmental sustainability. The purpose of this study is to determine the correlation between Green Intellectual Capital and Environmental Performance, with Green HRM serving as a mediator between the two variables. This study uses a quantitative methodology that utilizes the Structural Equation Modeling (SEM) technique, specifically the Partial Least Square (PLS) method. The research instrument used is SmartPls 4. The method used to select the sample is Probability Sampling, specifically utilizing the Simple Random Sampling strategy. This study uses a sample of 50 people who work in a company engaged in sharia-based financial services in the city of Surakarta. The results of this study indicate that Green Human Capital and Green Relational Capital have a significant impact on Green Human Resources, but have no impact on Environmental Performance. Green Structural Capital does not affect Green Human Resource Management, but has an impact on Environmental Performance.